PASSIVE SMOKING / INDOOR AIR QUALITY UPDATE - MILLMAN,AJ (Tufts Archival Research Center, 2007)
Document to be distributed from Amy J. Millman regarding the passive smoking/indoor air quality debate. Announces a three day hearing on a proposed bill which would limit smoking in government buildings to designated areas and gives the schedule for the three days. Includes summaries of other activities related to indoor air quality.